Alkali Metal Complexes: Mixed Ligand Complexes of Alkali Metal Salts of Some Organic Acids with o-Hydroxy Acetophenon Hydrazone - Mahmood, Shahnawaz; Sinha, P.C. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of alkali metal salts of organic acids, viz., acetylacetone, salicylaldehyde, anthranilic acid, picolinic acid and quinaldinic acid with o-hydroxy acetophenone hydrazone have been synthesized and characterised on the basis of elemental analyses, conductivity measurement and infra-red spectral data. The probable structure has also been assigned. Low values of molecular conductivity suggest the covalent nature of bond in these complexes.